Sono-myography and sono-myoelastography of the tender points of women with fibromyalgia - Muro Culebras, Antonio Luis; Cuesta-Vargas, Antonio (Elsevier, 2013)
Sono-myography and sono-myoelastography have been found useful in the investigation of myofascial trigger points. The objective of this study was to use the same techniques to investigate the morphology, stiffness and blood flow of tender points in women with fibromyalgia and to compare the results with those for samples from healthy patients. Algometry tests indicated significant differences between groups (p < 0.001). Elliptical and hypoechoic areas were observed in the ultrasound images of the upper trapezius in both groups. No differences between groups were found in the number of hypoechoic areas (p = 0.167, t = 1.008); blood flow also did not differ between the groups. Larger hypoechoic areas were found in the fibromyalgia group (p = 0.139, t = 1.317). Sono-myoelastography did not reveal greater stiffness in these areas compared with the rest of the muscle. These results lead us to believe that sono-myoelastography and sono-myography, used in the diagnosis of myofascial trigger points, may not be able to discriminate tender points.
Keywords: Fibromialgia; Fibromyalgia; Sonoelastography; Tissue elasticity; Ultrasound